Cryptosporidium Soil Extraction by Filtration/IMS/FA Compatible with USEPA Method 1623.1. Issue 1 (1st December 2016) - Zopp, Zachariah P.; Olstadt, Jeremy M.; Karthikeyan, K. G.; Thompson, Anita M.; Long, Sharon C.
Abstract : Core Ideas: Cryptosporidium extraction from the soil matrix is absent in USEPA Method 1623.1. Our S 3 PEG soil extraction is compatible with USEPA Method 1623.1. S 3 PEG extraction meets quality control recoveries specified by USEPA Method 1623.1. Irradiated Cryptosporidium oocysts are suitable soil surrogate for live oocysts. Cryptosporidium, a parasitic pathogen, when present in drinking water supplies poses a significant risk to human health. The soil environment provides a critical linkage between Cryptosporidium parent material (bovine manure) and the surface and groundwaters used by susceptible human populations for drinking water. The lack of a USEPA published analysis for the determination of Cryptosporidium in soil is a barrier to standardized investigation of Cryptosporidium transport in soils. Methodologies have been published in the absence of a USEPA analysis, yet they lack sufficient detail and quality controls to be generally applicable. This study developed and evaluated a Cryptosporidium soil extraction method capable of producing an extracted fluid containing Cryptosporidium that could be purified and enumerated using USEPA Method 1623.1.